1998
DOI: 10.1007/s001150050240
|View full text |Cite
|
Sign up to set email alerts
|

Schlafentzug und anschließende Schlafphasenvorverlagerung stabilisiert den positiven Schlafentzugseffekt bei depressiven Episoden

Abstract: Approximately 60% of patients with major depression disorder show a beneficial response to total sleep deprivation (TSD), but the positive effect of TSD is short, and naps or the following night's sleep destroy it. Various methods have been tried to stabilize the positive sleep-deprivation effect. A consecutive 1-week advance in the sleep phase stabilized mood in more than 50% of the sleep-deprivation responders. We examined 40 male patients with major depression who in addition to medical treatment took part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…It has been shown that approximately two thirds of the patients who react positively to total sleep deprivation (at least 30% reduction of 6-item Hamilton Depression Scale scores) can be maintained in a positive mood state for 1 week [Vollmann and Berger, 1993;Berger et al, 1997;Riemann et al, 1999]. These results have been confirmed by other groups [Albert et al, 1998;Benedetti et al, in press].…”
Section: Sleep and Sleep Phase Advance In Bipolar Depressionsupporting
confidence: 80%
“…It has been shown that approximately two thirds of the patients who react positively to total sleep deprivation (at least 30% reduction of 6-item Hamilton Depression Scale scores) can be maintained in a positive mood state for 1 week [Vollmann and Berger, 1993;Berger et al, 1997;Riemann et al, 1999]. These results have been confirmed by other groups [Albert et al, 1998;Benedetti et al, in press].…”
Section: Sleep and Sleep Phase Advance In Bipolar Depressionsupporting
confidence: 80%
“…Surprisingly, the response rates with a 3-days advance protocol were similar to those in earlier studies using a 6-days phase advance treatment after SD (Vollmann & , Berger et al 1997,Albert et al 1998, Riemann et al 1999). This is in agreement with a recent study by Benedetti and coworkers (2001) who investigated 30 depressive patients with SD and consecutive 3days phase advance and found that phase advance was able to sustain the antidepressant effect of SD.…”
Section: Discussionsupporting
confidence: 84%
“…It has been shown in several clinical trials that a "phase advance"of the sleep period after SD can prevent relapses in about 60 % of responders to SD (Souetre et al 1987, Vollmann & Berger 1993, Riemann et al 1996, Berger et al 1997, Albert et al 1998). The rationale behind the combination of SD with a consecutive phase advance is based on studies comparing partial SD during the first and the second half of the night (Wehr 1990 for overview) and on "nap" studies after SD in depressives (Wiegand et al 1987, Riemann et al 1993).…”
mentioning
confidence: 99%
“…The advanced sleep phase was then shifted to the normal phase position within 1 week. It was shown in several studies that this combined sleep deprivation and sleep phase advance therapy was able to maintain the positive effect of sleep deprivation in about 60–75% of the sleep deprivation responders (74–78), compared with a 40% response rate in a control condition (‘phase delay’) (see Fig. 6).…”
Section: Other Manipulations Of the Sleep–wake Cyclementioning
confidence: 93%